Emotional AI for Analyzing Psychological Patterns and Reducing Suicidal Ideation (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The increasing incidence of suicidal ideation is a critical societal challenge that demands innovative and multifaceted strategies for effective mitigation. This research investigates the potential of Emotional Intelligence (EI)-based computer applications to detect, analyze, and mitigate psychological suicidal ideation in individuals.The foundation of this study lies at the convergence of Emotional Intelligence (EI) and Artificial Intelligence (AI), where AI tools are enhanced with EI principles to create applications that can understand, interpret, and respond to users' emotional states. By leveraging cutting-edge technologies such as Natural Language Processing (NLP), Machine Learning (ML), and Sentiment Analysis, these applications can detect subtle indicators of distress or suicidal ideation within digital communication, providing opportunities for timely intervention.This paper offers an extensive review of Emotional Intelligence, focusing on its pivotal role in understanding and managing emotions, and how this can be applied within AI-driven systems. It thoroughly discusses the advantages and challenges of integrating EI with AI to address mental health crises like suicidal ideation, emphasizing the need for ethical and sensitive solutions.Additionally, the study delves into the methodologies behind creating these AI applications, offering evaluations of existing tools while assessing their real-world effectiveness. An important aspect of the research is the exploration of ethical and privacy issues involved in managing sensitive mental health data within such systems.The conclusion explores the societal impacts of EI-based computer applications, particularly their potential to enhance current mental health services and revolutionize mental health care. This research advocates for continuous innovation and improvement in the development of EI-based AI tools, ultimately aiming to offer more scalable, personalized, and effective mental health solutions.